1. E

    Trigonometrical equation

    Hi. I have a problem solving this trigonometrical equation: 6sin(pi+x)+cos(pi/2+x) if cosx=0.6 and 0<x<pi/2 If you can, please ask questions so that I try to answer them myself and solve the equation step by step. I'm not from an English speaking country, but I hope we have similar terms and...
  2. P


    sin(inverse)sin(-600)=?? can we take(sin(-2pi+x))
  3. Y

    Where did the trigonometrical functions come from???

    Hi, I was wondering... Surely, the trigonometrical functions began as mere observations about the proportions between the sides of right angled triangles. Probably people were just drawing triangles in the sand, measured the sides and dividing, noticing that similar angles gave similar...
  4. V

    Drawing trigonometrical graphs

    I need some help with drawing y=sin(x) and y=cos(x) graphs. For example I have y=sin(x + pi/6) and y=cos(3x). How to draw graphs of these trigonometrical functions? How to find out points x and y to draw? I know that first step is finding period of the function. But I don't know how to do that...
  5. S

    Prove the following trigonometrical identity-

    (1- tan x + sec x)/(1+tan x + sec x) = cos x/(1+sin x)
  6. J

    trigonometrical heighting??

    as part of a measurement scheme to monitor subsidence a target at P2 was mounted on the face of an embankment and observed from a theodolite at P1. Height of Collimation of theodolite at P1 zenith angle P1-P2 95d30m00s Coefficient of refraction (K) -0.28 R=6375km From the above compute...
  7. maybeline9216

    trigonometrical qn

    Given that cot q=-t, t>0 and 0° ≤q≤180° , find, in terms of t, (a) cosec q (b) tan(-q) (c) sin(90°-q ) for(b) is it -(-1/t) = -(1/-t) ?? im kinda confused.... also can anyone tell me how to derive the following formulas from the four quadrants mtd....(as i dun want to memorise the...
  8. Λ

    An logarithmic problem and an trigonometrical problem

    Hello :) I'd like an check on my answers for these two equations: 1 2ln(x) = ln(2 - x) + ln(1) 2 cos(-x) = sin (-x) | -2\pi \leq x \leq 2\pi Note: We're working in radians here ---- Ok the first one: 2ln(x) = ln(2 - x) + ln(1) ln(x^2) = ln(2 - x) + ln(1) ln(x^2) = ln(2 - x) x^2 = 2 - x...